Hubungan antara Kadar Serum Albumin Awal dengan Lama Rawat Inap dan Status Pulang Pasien Dewasa dl Rumah Sakit:: Tlte Relation of Admission Serum Albumin Levels on Length of Stay and Recovery among Adult Hospitalized Pat - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Speed of the healing process can be assumed as hospital length of stay, though patient with good nutritional status will have less length of stay. Several community studies reported a relationship between low serum albumin level and increasing risk of hospital death, nosocomial infection and length of stay (LOS). The aim of the study was to assess the relationship between admission serum albumin levels with LOS and recovery among adult hospitalized patients. This was a prospective observational study. Subject were adult, inpatient of internal and neurological unit in Sardjito, M. Jamil and Sanglah Hospital. Serum albumin level, total lymphocyte count (TLC), hemoglobin were used to assess nutritional status on admission. Energy intake was obtained using visual comstok method. It was revealed that average LOS in the low serum albumin (11,91 days) was significantly greater than those of high serum albumin (9,78 days). Respondents with low serum albumin had 1,89 times of risk of length of stay greater than those with high serum albumin. LOS was not significantly different among Neurological and Cancer respondent (by a multivariate regression). Neurological respondent with low serum albumin had 9,99 times greater risk of recovery than non neurological respondent with high serum albumin. It was concluded that serum albumin level on admission was not associated with recovery but was associated with LOS.